2021
DOI: 10.3390/ijerph18084175
|View full text |Cite
|
Sign up to set email alerts
|

Normative Data for Blood Pressure in Croatian War Veterans: A Population-Based Study

Abstract: Purpose: The current study aimed to investigate the normative data for blood pressure. Materials and Methods: From 2017 to 2020, 2032 men and women classified as ‘war veterans’ were recruited (mean age ± standard deviation (SD): 60.97 ± 7.98 years; mean stature: 172.50 ± 9.10 cm; mean body mass: 90.25 ± 36.45 kg; mean body-mass index: 29.66 ± 5.59 kg/m2; 29.9% women). Their systolic and diastolic blood pressures were measured three times. The procedure was carried out according to the American Heart Organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In this cross-sectional study, we recruited men and women aged 45–75 years, who participated in a homeland war between Croatia and Serbia from 1990 to 1995. More detailed information about the rehabilitation institution and specific programs done with war veterans are described elsewhere 32 . In brief, the Home for Croatian Veterans is a rehabilitation center established by the Ministry of Croatian Veterans specialized in improving quality of life and overall well-being.…”
Section: Methodsmentioning
confidence: 99%
“…In this cross-sectional study, we recruited men and women aged 45–75 years, who participated in a homeland war between Croatia and Serbia from 1990 to 1995. More detailed information about the rehabilitation institution and specific programs done with war veterans are described elsewhere 32 . In brief, the Home for Croatian Veterans is a rehabilitation center established by the Ministry of Croatian Veterans specialized in improving quality of life and overall well-being.…”
Section: Methodsmentioning
confidence: 99%
“…In this cross-sectional study, we recruited men and women aged 45–75 years, who participated in a homeland war between Croatia and Serbia from 1990 to 1995. More detailed information about the rehabilitation institution and specific programs done with war veterans are described elsewhere [ 21 ]. In brief, The Home for Croatian Veterans is an accommodation and rehabilitation institution established by the Ministry of Croatian Veterans with the intention of improving and strengthening the provision of comprehensive care for the veteran and suffering population.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to the general population, war veterans are at increased risk for developing hypertension [ 21 ], having lower levels of physical functioning and quality of life [ 22 ]. It has also been reported that veterans describe challenges in maintaining their physical performance [ 23 ], being more prone to cigarette smoking [ 24 ] and gaining weight [ 25 ], which are all independent predictors of hypertension and physical fitness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Вказують також на відмінності у стані здоров'я жінок і чоловіків [25,68], вікові відмінності [25,69]. Зокрема для пацієнтів з гіпертонією залежно від статі різниться зв'язок між воєнними стресовими факторами та ССЗ у пізньому віці, жінки більш чутливі до стресів, пов'язаних з війною [25].…”
Section: стресзумовлені гіпертензивні зміни за умов пандемії Covid-19unclassified